Open versus closed septorhinoplasty approaches for postoperative edema and ecchymosis - Sakallıoğlu, Öner; Cingi, Cemal; Polat, Cahit; Soylu, Erkan; Akyi?it, Abdulvahap; Söken, Hakan (Lippincott Williams and Wilkins, 2015)
Objective: The aim of this study was to compare periorbital edema and ecchymosis seen after closed (endonasal) and open (external) septorhinoplasty (SRP). Methods: In total, 50 patients undergoing hump extraction and osteotomies were allocated to 2 groups. Group 1 consisted of 25 patients who underwent closed SRP. Group 2 consisted of 25 patients who underwent open SRP. Operation time, amount of intraoperative bleeding, and complications were recorded. Scoring of eyelid edema and periorbital ecchymosis was evaluated on the first, third, and seventh postoperative days using a scale of 0 to 4 by the first author. Results: There was no statistically significant difference between the groups in terms of age, sex, or operation time. No significant difference was observed clinically or statistically in the scores of periorbital edema or ecchymosis between groups 1 and 2 on the first, third, and seventh postoperative days (P > 0.05). Conclusions: The authors observed no clinically or statistically significant difference in comparing periorbital edema and ecchymosis seen after closed and open SRP.
WOS: 000357569600128
PubMed ID: 26080189
Keywords: Complication; Ecchymosis; Edema; Osteotomy; Septorhinoplasty